THE EFL STUDENTS’ REACTION IN ENGLISH TEACHING MATERIALS: AN ANALYSIS OF GENDER REPRESENTATION IN ENGLISH TEXTBOOK - Hendriwanto Hendriwanto (University of Kuningan, 2018)
The role of teaching materials plays major contribution to the language development. The published materials bridge the content and the practice in the classroom. From the analysis it was found 25 images which represented the gender role in which man dominated in all chapters. The representative of image in the textbook employed the role of social background of what student perceived in the course book. The students perceived that the three images could represent their want. However, most images did not show students’ daily activities. In addition, the findings showed that students’ responses to the images in the textbooks had controversy related to the role of man and woman in the reality. Keywords: gender analysis, teaching materials, textbook analysis